2016
DOI: 10.1007/s00709-016-1033-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriomes of the corn leafhopper, Dalbulus maidis (DeLong & Wolcott, 1923) (Insecta, Hemiptera, Cicadellidae: Deltocephalinae) harbor Sulcia symbiont: molecular characterization, ultrastructure, and transovarial transmission

Abstract: In this study, we surveyed the bacteriome-associated microbiota of the corn leafhopper Dalbulus maidis by means of histological, ultrastructural, and molecular analyses. Amplification and sequencing of 16S rDNA genes revealed that the endosymbiont "Candidatus Sulcia muelleri" (Phylum Bacteroidetes) resides in bacteriomes of D. maidis. Phylogenetic analysis showed that the sequence was closely allied to others found in representatives of the subfamily Deltocephalinae. We failed to amplify other sequences as "Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The bacteriocyte-associated symbiotic bacteria of O. dissimilis were identified through the combination of results of histological, ultrastructural, and molecular analyses. Based on the characteristic structural and ultrastructural features of the symbionts residing in auchenorrhynchous Hemiptera (Bressan et al 2009 , 2013 ; Noda et al 2012 ; Brentassi et al 2017 ; Michalik et al 2014 ; Kobiałka et al 2015 , 2016 , 2017 ; Szklarzewicz et al 2016 ) as well as results of the fluorescence in situ hybridization with symbiont-specific probes (Fig. 5 a–c), the pleomorphic bacteria have been identified as Sulcia , the large, lobated ones as Vidania , and the large, elongated ones have been identified as Sodalis -like bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The bacteriocyte-associated symbiotic bacteria of O. dissimilis were identified through the combination of results of histological, ultrastructural, and molecular analyses. Based on the characteristic structural and ultrastructural features of the symbionts residing in auchenorrhynchous Hemiptera (Bressan et al 2009 , 2013 ; Noda et al 2012 ; Brentassi et al 2017 ; Michalik et al 2014 ; Kobiałka et al 2015 , 2016 , 2017 ; Szklarzewicz et al 2016 ) as well as results of the fluorescence in situ hybridization with symbiont-specific probes (Fig. 5 a–c), the pleomorphic bacteria have been identified as Sulcia , the large, lobated ones as Vidania , and the large, elongated ones have been identified as Sodalis -like bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogeny and classification of Deltocephalinae leafhoppers are still a subject under discussion [ 29 ]. As results of earlier studies have indicated that members of the subfamily Deltocephalinae are characterized by very diverse symbiotic systems [ 6 , 9 , 17 , 19 , 21 , 27 , 30 ], we expect that our study will provide further details on the ultrastructure, distribution, systematic affiliation, and mode of transmission between generations of their symbiotic associates. While F. septentrionalis , G. ventralis , and C. quadrinotata are common in Poland, O. ishidae is a species native to Southeast Asia and adventive in Europe [ 31 ].…”
Section: Introductionmentioning
confidence: 95%
“…The histological studies of Müller [ 16 ] and Buchner [ 14 ] as well as later ultrastructural and molecular analyses [ 4 7 , 10 , 17 21 ] have shown that auchenorrhynchans are, as a rule, colonized by at least two obligate symbiotic microorganisms. As all these symbionts provide essential amino acids to the host, they have been named “co-primary symbionts” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insect-associated microorganisms could be important mediators of interactions between insects and plants (Sugio, Dubreuil, Giron, & Simon, 2015;Hammer & Bowers, 2015, Wielkopolan & Obrępalska-Stęplowska, 2016. Some researchers have reported that simultaneous infection with different species of endosymbionts in the same host organism is a common phenomenon in several insect groups (Thao et al, 2000;Thao, Gullan, & Baumann, 2002;Russell et al, 2003;Ishii, Matsuura, Kakizawa, Nikoh, & Fukatsu, 2013;Krawczyk et al, 2015;El-Sayed et al, 2015;Ghosh, Bouvaine, & Maruthi, 2015;Brentassi et al, 2017). Different tissues in the body of the same host constitute different microenvironments for endosymbiont organisms.…”
Section: The Induction Mechanism Of Plant Galls By Insects: What Do Wmentioning
confidence: 99%
“…Accumulated evidence shows that many species of arthropod are infected by different kinds endosymbiont organisms transmitted from the mother through vertical transmission, which have a great influence on the biology of their hosts. Some of these endosymbiont microorganisms include Wolbachia, Spiroplasma, Rickettsia, Arsenophonus, and Cardinium, among others (Weeks, Velten & Stouthamer, 2003;Zchori-Fein & Perlman, 2004;Goto et al, 2006;Casper-Lindley et al, 2011;Goodacre & Martin, 2012;Kageyama, Narita, & Watanabe, 2012;Koga et al, 2012;Kremer et al, 2012;Herren, Paredes, Schüpfer, & Lemaitre, 2013;Ma, Vavre & Beukeboom, 2014;Boivin et al, 2014;Ma et al, 2015;Sugio et al, 2015;Brentassi et al, 2017;Mariño, Verle Rodrigues, & Bayman, 2017;Ma & Schwander, 2017).…”
Section: The Induction Mechanism Of Plant Galls By Insects: What Do Wmentioning
confidence: 99%